Real Exchange Rate and Economic Growth in Tunisia - Souibgui, Moez; Abida, Zouheir (Journal of Ecohumanism, 2025)
This study examines the relationship between the real effective exchange rate (REER) and economic growth in Tunisia from 1980 to 2011, using the Generalized Method of Moments (GMM). The analysis incorporates key macroeconomic variables, including initial GDP per capita, investment, public expenditure, trade openness, and human capital, to assess their impact on economic performance. The results indicate that real exchange rate depreciation has a negative but statistically insignificant effect on growth. While depreciation may enhance external competitiveness and stimulate exports, its impact remains contingent on import costs and inflationary pressures. Conversely, trade openness and human capital have positive and statistically significant effects, reinforcing the argument that economic liberalization and investment in human capital are crucial drivers of growth. Public expenditure, however, shows a negative and significant relationship with growth, suggesting potential inefficiencies in fiscal policy. These findings highlight the importance of exchange rate management, investment policies, and trade liberalization in fostering economic development. Policymakers should prioritize structural reforms, technology transfer, and private investment to enhance long-term growth prospects. The study’s insights are particularly relevant for other developing economies seeking to optimize exchange rate policies and economic strategies to achieve sustainable growth.